Preparing Students for Change: An Advisement Seminar Informed by Tolman and Kremling's Integrated Model of Student Resistance. Issue 1 (3rd January 2023) - Dulek, Jeni; Gorenberg, Michelle; Hill, Kaylinn; Walsh, Kelsey; Perkins, Molly
Abstract: Graduate students entering entry-level occupational therapy programs are confronted by new ways of learning and interacting for which they may be ill-prepared. Confronted with the need to change their approach to learning, students may become frustrated and lose motivation, resulting in resistance. This article describes a pilot first term group advisement seminar, informed by Tolman and Kremling. Integrated Model of Student Resistance (IMSR), and designed to prepare students for these necessary changes. The article describes topics addressed, strategies implemented, and insights and reflections on the process and outcomes of participation in the seminar.